Case Report: Disruption of Resting-State Networks and Cognitive Deficits After Whole Brain Irradiation for Singular Brain Metastasis - Kocher, Martin; Jockwitz, Christiane; Lerche, Christoph; Sabel, Michael; Lohmann, Philipp; Stoffels, Gabriele; Filss, Christian; Mottaghy, Felix M.; Ruge, Maximilian I.; Fink, Gereon R.; Shah, Nadim J.; Galldiks, Norbert; et al. (Frontiers in Neuroscience, 2021)
Introduction: Long-term survivors of whole brain radiation (WBRT) are at significant risk for developing cognitive deficits, but knowledge about the underlying pathophysiological mechanisms is limited. Therefore, we here report a rare case with a singular brain metastasis treated by resection and WBRT that survived for more than 10 years where we investigated the integrity of brain networks using resting-state functional MRI. Methods: A female patient with a left frontal non-small cell lung cancer (NSCLC) brain metastasis had resection and postoperative WBRT (30.0Gy in 3.0Gy fractions) and stayed free from brain metastasis recurrence for a follow-up period of 11years. Structural magnetic resonance imaging (MRI) and amino acid (O-(2-[18F]fluoroethyl)-L-tyrosine) positron emission tomography (FET-PET) were repeatedly acquired. At the last follow up, neurocognitive functions and resting-state functional connectivity (RSFC) using resting-state fMRI were assessed. Within-network and inter-network connectivity of 7 resting-state networks were computed from a connectivity matrix. All measures were compared to a matched group of 10 female healthy subjects. Results: At the 11-year follow-up, T2/FLAIR-MR images of the patient showed extended regions of hyper-intensities covering mainly the white mater of the bilateral dorsal frontal and parietal lobes while sparing most of the temporal lobes. Compared to the healthy subjects, the patient performed significantly worse in all cognitive domains that included executive functions, attention and processing speed, while verbal working memory, verbal episodic memory, and visual working memory were left mostly unaffected. The connectivity matrix showed a heavily disturbed pattern with a widely distributed, scattered loss of RSFC. The within-network RSFC revealed a significant loss of connectivity within all 7 networks where the dorsal attention and fronto-parietal control networks were affected most severely. The inter-network RSFC was significantly reduced for the visual, somato-motor, and dorsal and ventral attention networks. Conclusion: As demonstrated here in a patient with a metastatic NSCLC and long-term survival, WBRT may lead to extended white matter damage and cause severe disruption of the RSFC in multiple resting state networks. In consequence, executive functioning which is assumed to depend on the interaction of several networks may be severely impaired following WBRT apart from the well-recognized deficits in memory function.